2008
DOI: 10.1007/s00702-008-0164-y
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating nicotine- versus schizophrenia-associated decreases of the α7 nicotinic acetylcholine receptor transcript, CHRFAM7A, in peripheral blood lymphocytes

Abstract: Nicotine addiction is prevalent in individuals with schizophrenia. Nicotine activation of nicotinic receptors (nAChRs) is time- and dose-dependent, but gene expression analyses often rely on qualitative self- or family-reported measures of smoking. We sought lymphocyte surrogates for cerebral alpha7-nAChR activity and tested if receptor transcription correlated with concurrently measured serum biomarkers for smoking [cotinine, C-reactive protein (CRP)]. PCR surveys to detect lymphocytic alpha7-related isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
2
11
1
Order By: Relevance
“…Additionally, our findings that nicotine markedly reduces the expression levels of dup␣7 mRNA in MØ (Fig. 7C) are in complete agreement with recent in vivo results showing a lower ␣7 transcript expression in PBMC from smokers than from nonsmokers (57). Further experiments are needed to learn whether cerebral dup␣7 mRNA expression can be regulated by different stimuli, as occurs in MØ.…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, our findings that nicotine markedly reduces the expression levels of dup␣7 mRNA in MØ (Fig. 7C) are in complete agreement with recent in vivo results showing a lower ␣7 transcript expression in PBMC from smokers than from nonsmokers (57). Further experiments are needed to learn whether cerebral dup␣7 mRNA expression can be regulated by different stimuli, as occurs in MØ.…”
Section: Discussionsupporting
confidence: 80%
“…However, enhanced CHRNA7 expression did not render human whole blood monocytes more susceptible to nicotinic immunomodulation, which may indicate that the CHRNA7 is not the only mediator effectuating the cholinergic anti-inflammatory effect and another nAChR might be involved. For example, the finding that CHRFAM7A is downregulated in monocytes by LPS challenge, and has been found to be downregulated in smokers’ PBMCs [32] suggests that it could play a role in inflammation by affecting functional α7 nAChRs [14]. This is in conjunction with earlier studies in which it was put forward that receptors of mixed subunits of CHRNA7 and CHRFAM7A are formed that can modulate the signaling potential of immune cells to respond to ACh released from the vagus nerve during infection [12].…”
Section: Discussionmentioning
confidence: 99%
“…None of the splice variants was detected, thereby confirming that dupa7nAChR/ CHRFAM7A Variant 1 is the major transcript in human leukocytes. Furthermore, when analyzing blood from 20 patients, they found that whereas the presence of dupa7nAChR/ CHRFAM7A was readily detectable in human leukocytes, a7nAChR/CHRNA7 was not [76]. Interestingly, they also evaluated dupa7nAChR/CHRFAM7A expression levels in smokers and reported significantly (P , 0.001) decreased dupa7nAChR/CHRFAM7A expression.…”
Section: The Main Chrna7 Transcript Detected By Pcr Of Human Leukocytmentioning
confidence: 99%
“…Four years after Villiger et al [48] identified dupa7nAChR/ CHRFAM7A in human PBMCs, Perl et al [75] would inadvertently confirm the differential expression of dupa7nAChR/ CHRFAM7A and a7nAChR/CHRNA7 in human leukocytes by use of sequence-specific primers that distinguish a7nAChR/ CHRNA7 from dupa7nAChR/CHRFAM7A on human blood samples. Soon thereafter, Severance et al [76] would be the 1st to combine sequence-specific primers and quantitative PCR to quantify a7nAChR/CHRNA7, a7nAChR/CHRNA7 splice variants (e.g., exon 4 deletion, exon 5 deletion, exon 4 and 5 deletion, and exon 4a insertion), and dupa7nAChR/ CHRFAM7A expression in human PBMCs. None of the splice variants was detected, thereby confirming that dupa7nAChR/ CHRFAM7A Variant 1 is the major transcript in human leukocytes.…”
Section: The Main Chrna7 Transcript Detected By Pcr Of Human Leukocytmentioning
confidence: 99%